Common Diseases of Children in Urban Community Health Service Institutions - Delu YIN, Xi WANG, Tao YIN (Zhongguo quanke yixue, 2022)
Background In 2019, the National Health Commission issued the Capacity Standards for Community Health Service Center (2018 version), which proposed that the 56 common disease species should be offered diagnosis and treatment services by CHSC, but it did not specify the common disease species of children in the community, which to some extent affects the assessment and construction of CHSC capacity in the community. Objective To investigate and analyze the common childhood disease species and their characteristics in community health services, in order to provide a reference basis for further community child health service capacity building. Methods In April 2020, a convenience sampling method was adopted to select community health service agencies in 11 different level cities in China as the sample unit. A self-designed questionnaire was administered to cover the subject's basic condition, the common childhood disease conditions suitable for diagnosis and treatment in the community, and their sequencing. Filled out online voluntarily anonymously by child health service personnel at the sample institution, 3 090 cases were successfully investigated. Respondents ranked the common degree of children's related disorders from low to high, assigning 1 to 5 points to each of the top 5 common childhood disorders, which is, assigning 5 points to ranked 1, 1 point to ranked 5, and 0 points to unselected, calculating a total and sorting by total score. Results The top 5 disease categories for children in the community were acute upper respiratory infection, diarrhea, bronchitis, pneumonia, and eczema. Of the top 10 ranked community common childhood disorders, 3 were respiratory, 3 were facial and dermatologic, 2 were infectious, and 1 each was a digestive and growth and development related disorder. The top 5 common childhood diseases ranked by different regions, different levels of cities and different posts were consistent, but the ranking order was different, but there were differences in the 6th-10th disease species and order. Conclusion The current coverage of common childhood diseases in community health services is high. There is regional, urban, and post heterogeneity in common childhood disease species in communities. Construction of community child health service capacity should be oriented to improve the capacity of diagnosis and treatment service of common childhood diseases in the community, and fully consider the disease species variability in different regions, cities, and posts.